Edukacja artystyczna w Polsce. Perspektywy rozwoju edukacji przez sztuki wizualne - Bugajska-Bigos, Iwona (Warstwy, 2021)
The article is an attempt to take a stand on art education in the Polish educational system. The author analyzes art education in primary school and its further stages in secondary and higher education, with particular attention to dynamic changes in this regard. The article also presents new phenomena and tendencies in art. education as well as various solutions in extracurricular education. The text also considers the latest situation: e-learning brought about by the pandemic. Selected examples of systemic solutions, support granted to art. education and understanding its role in other countries, show differences in this respect, which may initiate a wide debate about the need to change the perception, availability and opportunity of development of art. education.